Zmiana struktury organizacyjnej Zachodniopomorskiego Centrum Edukacyjnego w Szczecinie warunkiem wdrożenia controllingu - Rosiak, Janina; Szczypa, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the article have been presented solutions, which are directed on fitting of organizationalstructure of West Pomeranian Educational Center in Szczecin for requirements of implementation ofcontrolling. The analyzed school must take attempt of change of system of management and there isone of possible solution - controlling. However, forceful implementation of controlling requires thechanges in present organizational structure of school. (orginal abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 359-365